Diversidad, bioformas y abundancia de plantas acuáticas en humedales de las llanuras inundables del Orinoco en Venezuela (2014)
Richness (alpha and beta diversity), abundance and dominance of bioforms of aquatic vegetation in a wetland of the Orinoco floodplains in Venezuela, studied over an annual cycle are described. In a lowland extension of 65,000 hectares including a whole range of aquatic habitats (shallows, marshes, ponds and streams), 197 species belonging to 122 genera and 56 families were recorded. Beta diversity was higher in lentic than in lotic wetlands, the emergent rooted bioform being the most abundant in all habitats and throughout the year. Considering the most persistent species (spatially and temporally), Eichhornia crassipes (Mart) Solms., Hymenachne amplexicaulis (Rudge) Nees and Luziola subintegra Swallen obtained the highest relative importance values. The most abundant species in all environments and throughout the year was Salvinia auriculata Aubl. Brief comments on the limited use of these aquatic plants are given.